STUDI SISTEM PEMELIHARAAN REL KERETA API (STUDI KASUS : PETAK JALAN PAYAKABUNG – SERDANG) - Nuryaman, Maman; Firdaus, Firdaus (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
The railway track maintenance system on the Payakabung – Serdang segment aims to identify the condition of track materials, evaluate the applied maintenance system, and analyze the Track Quality Index (TQI) as an indicator of track quality. This research applies a quantitative approach by collecting primary data on track material conditions and secondary data such as train traffic frequency, inspection schedules, and TQI values. The analysis was carried out descriptively through tables, graphs, and technical calculations.The study found several types of track damage, including defective rails (55 points), broken sleepers (27 units), loose joint bolts (60 units), installed fishplates (16 points), and ballast shortages of 200 m³ at several locations. The most dominant damages were defective rails, broken sleepers, and loose joint bolts. Based on the calculation, the line capacity reached 15,190,956 tons/year, categorized as Class II track with UIC 5 classification. The total TQI value indicates that the track condition is still in the good category, although the maintenance system tends to be more corrective than preventive.The railway track maintenance on the Payakabung – Serdang segment has been carried out through regular inspections and periodic repairs. However, preventive measures need to be improved to maintain consistent track quality and ensure the safety of train operations.Keywords: Track maintenance, railway track, Track Quality Index (TQI), Payakabung – Serdang.